Identification and Management of Distributed Data: NGN, Content-Centric Networks and the Web - Bartolomeo, Giovanni (CRC Press, 2013)
This book guides readers through the discovery of distributed data management on the web, in next generation networks (NGNs), and in new content-centric networking paradigms. The authors provide a novel perspective with particular emphasis on naming and identification issues, which are concepts that must be grasped in order to build and deploy more efficient data interoperability paradigms in future networks. The book covers special insights, ongoing research projects, and standardization initiatives.